Trauma Psikologis Dalam Antologi Puisi Aku Ini Binatang Jalang Karya Chairil Anwar: Kajian Psikologi Sastra - Musdalifa Musdalifa; Ahmad Ghazali Samad; Siti Hasriyati Anies; Sintia Syarif (AIJER: Algazali International Journal Of Educational Research, 2025)
This study aims to identify the psychological trauma reflected in the collection of poems by Chairil Anwar based on Carl Gustav Jung’s theory, namely the personal unconscious, the collective unconscious, and complexes. This research employs a qualitative descriptive method, which examines in depth the forms of psychological trauma based on the personal unconscious, the collective unconscious, and complexes. The data source of this study is a collection of poems by Chairil Anwar entitled Aku Ini Binatang Jalang, published by Gramedia Pustaka Utama in Jakarta in 1986. The data collection techniques used in this study are observation and documentation, in the form of notes or photographic records from the poetry collection Aku Ini Binatang Jalang by Chairil Anwar that are relevant to this research. The results of this study indicate that psychological trauma is reflected in Chairil Anwar’s poems through the dimensions of the personal unconscious, the collective unconscious, and complexes. The personal unconscious refers to personal experiences that have been repressed or forgotten but still influence an individual’s behavior. The collective unconscious refers to universal human experiences that are inherited across generations. Meanwhile, complexes refer to clusters of emotionally charged ideas or observations centered on particular themes that exert a strong influence on an individual.